TREATMENT OF CLINICAL ANOESTRUS IN ARABIAN MARES BY A PROSTAGLANDIN F2 α|ή‎|‎ωϧΔΔ ‎‎|‎ ‎ - F.R., Abdul-Aziz,; H.A. , Fahmi, (The Iraqi Journal of Veterinary Medicine, 1987)
A synthetic prostaglandin F2 α(PGF2 α) analogue, luprostiol* , was used in treatment of clinically anoestrus Arabian mares that suffered from abnormal persisting luteal function. Thirty two anoestrus mares were selected for this study after careful examination of their breeding history and a thorough genital examination which included rectal palpation of the genital tract and ovaries. The genital examination also included a vaginoscopy of the vagina and cervix. These mares were diagnosed as clinically anoestrus during the spring and summer months breeding season and received a single intramuscular injection of the prostaglandin F2 α. Twenty six mares (81%) responded to the treatment and came to oestrus within 2-4 days. Ovarian activity of the induced oestrus was monitored by rectal palpation and the mares were bred twice according to their follicular development. A total of 13 mares (54%) became pregnant as a result of the treatment and pregnancies were confirmed later by rectal palpation. This study reveals that the majority of non-cycling mares during the spring and summer months breeding season are in a prolonged luteal function rather than inactive ovaries or ‘true anoestrus. The study also demonstrates the efficiency of Iuprostiol in the treatment of clinically anoestrus mares.